2015
DOI: 10.1039/c5tc02318a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and thermoelectric properties of Sr–Mo substituted CaMnO3: a combined experimental and computational study

Abstract: Experimental and modelling investigation of Sr/Mo (co-)doped CaMnO3 highlighted the role of Mn3+ and presence of domain boundaries in thermal transport and thermoelectric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 61 publications
3
19
1
Order By: Relevance
“…ZnO ~ -300 µV/K, 61 and CaMnO 3 ~ -200 µV/K, 46,62 respectively. Interestingly, the change in the values of Seebeck coefficient observed at ~480 K coincides with the transition from the orthorhombic to tetragonal structure.…”
Section: Electronic and Thermal Transport Propertiesmentioning
confidence: 99%
“…ZnO ~ -300 µV/K, 61 and CaMnO 3 ~ -200 µV/K, 46,62 respectively. Interestingly, the change in the values of Seebeck coefficient observed at ~480 K coincides with the transition from the orthorhombic to tetragonal structure.…”
Section: Electronic and Thermal Transport Propertiesmentioning
confidence: 99%
“…Although CaMnO 3 has relatively high Seebeck coefficient, its electrical conductivity is very low (0.1 to 1 S/cm in the temperature range 300-1000 K), which often results in low PF values [64]. Previous studies indicated that with a minor electron ), its electrical conductivity can be significantly increased.…”
Section: Camnomentioning
confidence: 99%
“…The signicant increase of Mn 4+ content aer 3000 cycles may be responsible for the dramatic reduction of specic capacitance by weakening the electron conductivity, as reported in other publications. [53][54][55] To further evaluate the practical application of the assynthesized materials for supercapacitor, a solid-state asymmetric supercapacitor (ASC) was assembled to test its electrochemical performances, using KMF02 as positive electrode and activated carbon (AC) as negative electrode, respectively. The construction of ASC is illustrated in Fig.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%